2006
DOI: 10.1002/jat.1184
|View full text |Cite
|
Sign up to set email alerts
|

Methodological aspects on measurement of Clara cell protein in urine as a biomarker for airway toxicity, compared with serum levels

Abstract: The Clara cell protein CC16, secreted from Clara cells in the lung, is discussed as a potential biomarker for toxic effects on the airways. An increased concentration of CC16 in serum may be caused by increased permeability of the lungs, caused by high levels of air pollution. Since CC16 is eliminated by renal excretion, it may be possible to use urine instead of serum samples. Few studies have been conducted on urinary CC16 (U-CC16), however. The aim was to investigate the optimal way of sampling and quantify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
37
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 10 publications
4
37
0
1
Order By: Relevance
“…9 Urine biomarkers offer several advantages compared with serum samples, as they simplify collection, reduce costs, and may decrease participant attrition. 30 In addition, biomarkers can shed light on the mechanisms of disease pathogenesis. In the present study, an inverse association was found between urine levels of CC16 at the time of an infant LRTI and the odds of subsequent childhood wheeze.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…9 Urine biomarkers offer several advantages compared with serum samples, as they simplify collection, reduce costs, and may decrease participant attrition. 30 In addition, biomarkers can shed light on the mechanisms of disease pathogenesis. In the present study, an inverse association was found between urine levels of CC16 at the time of an infant LRTI and the odds of subsequent childhood wheeze.…”
Section: Discussionmentioning
confidence: 99%
“…Urine levels of CC16 could be also affected by several other factors (e.g., post-renal excretion of CC16, diurnal variation, and physical activity). 13,30,53 However, it is unknown if these factors are truly important in children, as the limited data available are in adults. 13,14 Furthermore, urine levels of CC16 have been highly correlated to serum levels (which are less likely to be affected by some of these factors) in other studies using a similar instrument.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations